2021
DOI: 10.1002/pat.5395
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shielding of electromagnetic radiations with flexible, light‐weight, and conductive Ag‐Cu/MWCNT/rGO architected PVDF nanocomposite films

Abstract: High performance electromagnetic interference (EMI) shielding materials with ultra‐low density, excellent flexibility with comprehensive nature are highly demanded for wearable electronics, aeronautic, industries, medical, and research facilities. To address these requirements, the metal‐carbon based polymer composites have been fabricated by simple and scalable synthesis techniques. Combining the effect of multiple scattering with absorption, a high shielding efficiency of up to 29 dB for 0.1 mm is achieved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…34 The Ag−Cu/CNT/graphene/PVDF composite films prepared by Rengaswamy et al via solvent casting technology showed an EMI SE performance of 29 dB at 0.1 mm. 35 36 Considering the high EMI SE property of pure graphene (which can reach as high as 135 dB), further improving the EMI SE performance of graphene-based flexible composites on the premise of ensuring their flexibility is worth the effort. As known, increasing either the thickness or the conductive filler content can improve the EMI SE performance of the composite, but at the cost of its flexibility and ductility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The Ag−Cu/CNT/graphene/PVDF composite films prepared by Rengaswamy et al via solvent casting technology showed an EMI SE performance of 29 dB at 0.1 mm. 35 36 Considering the high EMI SE property of pure graphene (which can reach as high as 135 dB), further improving the EMI SE performance of graphene-based flexible composites on the premise of ensuring their flexibility is worth the effort. As known, increasing either the thickness or the conductive filler content can improve the EMI SE performance of the composite, but at the cost of its flexibility and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many flexible EMI SE composites based on PVDF have been developed for potential practical applications. It is reported that the EMI SE performance of Ag/graphite/PVDF flexible composite films prepared by Kumaran et al via embedding Ag nanoparticles into graphite was measured to be 29.1 dB at 12.4 GHz . The Ag–Cu/CNT/graphene/PVDF composite films prepared by Rengaswamy et al via solvent casting technology showed an EMI SE performance of 29 dB at 0.1 mm . Zhao et al filled 15 wt % graphene into PVDF matrix, and the composite film synthesized by solution casting and molding exhibited good flexibility and 22.58 dB in EMI SE performance at 0.1 mm thickness .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] GNP is also a preferable conductive medium with superior thermal stability. [26][27][28] Similarly, related studies have shown that GNP has a direct effect on electromagnetic radiation shielding, 29,30 which suggests that GNP has promising applications in composite modification. The addition of graphene oxide (GO) is increasingly applied in polymer nanocomposites to tailor their properties further.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of dielectric and magnetic fillers, the absorption percentage during shielding can be enhanced. [32][33][34] Epoxy/CF composites with CF modification have been extensively studied by researchers in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of dielectric and magnetic fillers, the absorption percentage during shielding can be enhanced. 32–34 Epoxy/CF composites with CF modification have been extensively studied by researchers in the last decade. Gholampoor et al 35 prepared nano-Fe 3 O 4 powder via a co-precipitation method and deposited this on CFs using an electrophoretic deposition (EPD) method; it was then incorporated into epoxy.…”
Section: Introductionmentioning
confidence: 99%